Obstetric consequences of a false‐positive diagnosis of large‐for‐gestational‐age fetus. Issue 3 (9th December 2021) - Papaccio, Marta; Fichera, Anna; Nava, Alessia; Zatti, Sonia; Gerosa, Vera; Ferrari, Federico; Sartori, Enrico; Prefumo, Federico; Fratelli, Nicola
Abstract: Objective: To compare delivery outcomes between true‐positive (TP) and false‐positive (FP) large‐for‐gestational‐age (LGA) fetuses, appropriate‐for‐gestational‐age (AGA) fetuses, and false‐negative (FN) LGA fetuses. Methods: Retrospective cohort study of singleton pregnancies at risk for macrosomia without contraindication to vaginal delivery, receiving an ultrasound scan at 34–37 weeks of pregnancy. Results: In all, 430 pregnancies were included: 155 TP LGA, 87 FP LGA, 177 AGA and 11 FN LGA newborns. Cesarean section rate during labor was significantly higher in FP LGA than in AGA (19% vs. 8.7%) but not significantly different between FP LGA and TP LGA (19% vs. 32.4%). Median birth weight z score was significantly higher in TP LGA (1.9) compared with the FP LGA and AGA (0.91 and 0.84, respectively), whereas no significant differences were found between FP LGA and AGA. Admission to a neonatal intensive care unit was significantly more frequent in TP LGA than AGA, whereas shoulder dystocia, postpartum hemorrhage, and third‐ to fourth‐degree perineal tears were similar between the different groups. Conclusion: A false‐positive diagnosis of LGA fetus is associated with a significant increase of cesarean section during labor. Therefore, a suspicious ultrasound may result in reduction of the clinical threshold for the diagnosis of abnormal labor. Abstract : A false‐positive diagnosis of LGA fetus on ultrasound at 34–37 weeks is associated with a significant increase in cesarean section during labor.